2013
DOI: 10.1021/jp404321f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Formate Adsorption and Protons on Shallow Trap Infrared Absorption (STIRA) of Anatase TiO2 During Photocatalysis

Abstract: ATR-IR spectroscopy has been used to probe the spectral changes resulting from UV irradiation of thin particulate films of anatase TiO2 under aqueous anoxic conditions. Irradiation under circumneutral solutions removed adsorbed impurities and produced a transient broad IR absorption peaking at ∼880 cm–1 that has been attributed to excitations associated with shallow electron traps. This shallow trap IR absorption (STIRA) was long-lived under acidic conditions with peak absorbance rising with decreasing pH. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 91 publications
3
45
1
Order By: Relevance
“…In aqueous solutions, the electron charging of a nc-TiO 2 material associates with proton participations, so observing gap states by optical absorptions is affected by proton intercalation. McQuillan et al found a pH-dependent mid-IR absorption peaked at 880 cm −1 in an aqueous solution under excitation with UV light illumination [312]. This peak does not correspond to the Drude-like free electron absorption and the phonon modes of TiO 2 .…”
Section: Transient Optical Absorptionsmentioning
confidence: 99%
“…In aqueous solutions, the electron charging of a nc-TiO 2 material associates with proton participations, so observing gap states by optical absorptions is affected by proton intercalation. McQuillan et al found a pH-dependent mid-IR absorption peaked at 880 cm −1 in an aqueous solution under excitation with UV light illumination [312]. This peak does not correspond to the Drude-like free electron absorption and the phonon modes of TiO 2 .…”
Section: Transient Optical Absorptionsmentioning
confidence: 99%
“…These peaks could be assigned to the CO stretching mode of HCO 3 À . 33 Since CO 2 in air was dissolved in solution as a form of HCO 3 À , it photoadsorbed on the surface of TiO 2 . The broad signal ranging from 1100 to 900 cm À1 could be attributed to Ti-OO À based on the spectral change with H 2 O 2 in the following experiments and the spectra in D 2 O (Fig.…”
Section: Change Of Tio 2 Surfaces Upon Irradiationmentioning
confidence: 99%
“…Electron excitation from these states to the conduction band and inter-conduction-band transitions (Drude-type absorption) were proposed to contribute to the broad IR signal. 11 , 12 Interestingly, such IR signals were detected not only under high-vacuum conditions but also upon band gap excitation of TiO 2 in contact with aqueous solutions of hole acceptors 13 , 14 and upon cathodic polarization in acidic aqueous electrolytes. 14 17 …”
Section: Introductionmentioning
confidence: 98%